EFEKTIVITAS KOMPOS PADA MEDIA TANAH TERCEMAR LIMBAH OLI BEKAS DENGAN AGEN FITOREMEDIASI TREMBESI (Samanea saman) - Setia Budi, Widia Arum; Asmarahman, Ceng; indriyanto, Indriyanto (MAKILA, 2024)
Used oil is included in B3 waste (hazardous and toxic materials) which can cause soil pollution and reduce soil productivity. Careless disposal of used oil waste results in soil pollution and reduces soil productivity, so ways are needed to improve the condition of the soil. One way is through phytoremediation techniques using the trembesi plant, with soil amendments as compost. This research aims to analyze the effect of compost on the growth of trembesi plants on soil contaminated with used oil waste. This research used a Completely Randomized Design (CRD) with compost fertilizer factors consisting of 3 dose levels and a total of 45 samples of observation units. The results of the research showed that the treatment dose of compost that had the best effect on the growth of trembesi in soil contaminated with used oil waste was a dose of 120 ml, which was proven to increase the growth of trembesi seedlings on the diameter parameter and the dose of 60 ml was proven to increase the growth of trembesi seedlings on the parameters of several root nodules and an adequate number of root nodules.